Nutrient and herbivore alterations cause uncoupled changes in producer diversity, biomass and ecosystem function, but not in overall multifunctionality - Alberti, Juan (2017)
Altered nutrient cycles and consumer populations are among the top anthropogenic influences on ecosystems. However, studies on the simultaneous impacts of human-driven environmental alterations on ecosystem functions, and the overall change in system multifunctionality are scarce. We used estuarine tidal flats to study the effects of changes in herbivore density and nutrient availability on benthic microalgae (diversity, abundance and biomass) and ecosystem functions (N2-fixation, denitrification, extracellular polymeric substances -EPS- as a proxy for sediment cohesiveness, sediment water content as a proxy of water retention capacity and sediment organic matter). We found consistent strong impacts of modified herbivory and weak effects of increased nutrient availability on the abundance, biomass and diversity of benthic microalgae. However, the effects on specific ecosystem functions were disparate. Some functions were independently affected by nutrient addition (N2-fixation), modified herbivory (sediment organic matter and water content), or their interaction (denitrification), while others were not affected (EPS). Overall system multifunction remained invariant despite changes in specific functions. This study reveals that anthropogenic pressures can induce decoupled effects between community structure and specific ecosystem functions. Our results highlight the need to address several ecosystem functions simultaneously for better ecosystem characterization and management.